Pengaruh Penerapan Pendekatan Matematika Realistik Terhadap Kemampuan Berpikir Kritis Siswa - Arinta Rara Kirana; Partasiwi, Nurashri (Lentera: Jurnal Ilmiah Kependidikan, 2023)
The problem in this study is the low critical thinking skills of students in learning mathematics. The purpose of this study was to determine the effect of applying a realistic mathematical approach to the critical thinking skills of Class X Even Semester students at SMK Negeri 7 Bandar Lampung in the 2022/2023 academic year. This study used an experimental method with the population in this study, namely all students in class X even semester of SMK Negeri 7 Bandar Lampung, while two classes were taken, namely class X KK 1 which used a realistic mathematics approach, and class X KK 2 which used a conventional approach. Samples were taken using the Cluster Random Sampling technique. To find out students' critical thinking skills, a test was carried out in the form of an essay of five questions which had previously been tested for validity and reliability. Hypothesis testing in this study uses the t-hit formula. From the results of testing the hypothesis using the t-hit statistical formula, the value of t = 1,88 is obtained. From the t distribution table at a significant level of 5% it is known that t = 1,67 then  which means that the average critical thinking ability of students who use a realistic mathematics approach is higher than the average critical thinking ability of students who use a conventional approach.